TRANSFORMASI PENGAKUAN HAK MASYARAKAT ADAT DALAM BINGKAI HAM: STUDI KASUS PENETAPAN HUTAN ADAT GHIMBE PERAMUNAN DI KABUPATEN MUARA ENIM - Henni Martini; Mira Shintia; Selvita Andriani; Jose Daniel Vargas (STKIP Subang, 2026)
The recognition of indigenous law communities and their traditional rights over forests is a key indicator of democratization progress and human rights protection in Indonesia. Following the Constitutional Court Decision Number 35/PUU-X/2012, the state has opened space for indigenous peoples to gain legal rights over customary forests they have managed for generations. This article aims to analyze the process and implications of recognizing indigenous peoples' rights over the Ghimbe Peramunan Customary Forest, managed by the Puyang Sure Aek Bigha Indigenous Law Community in Penyandingan Village, Semendo Darat Laut District, Muara Enim Regency, South Sumatra. Using a qualitative method with a case study approach, this research finds that the recognition, initiated by the Muara Enim Regent's Decree Number 964 of 2018 and followed by the Minister of Environment and Forestry Decree Number SK.3758/MENLHK-PSKL/PKTHA/PSL.1/3/2019, is a significant achievement in the decentralization of natural resource management. This process was multi-stakeholder collaboration, including local government, the Ministry of Environment and Forestry, and accompanying NGOs such as the Hutan Kita Institute (HaKI). However, this legal recognition is merely the entry point. The subsequent main challenges lie in strengthening the institutional capacity of the indigenous community, developing sustainable productive economies, and resolving post-determination administrative issues. The study concludes that the recognition of the Ghimbe Peramunan customary forest represents progress in the democratization of forest governance based on the recognition of human rights, although its sustainability requires consistent policy support and continuous assistance to ensure ecological and socio-economic benefits can be realized.